A Large Intrathoracic Hiatal Hernia as a Cause of Complete Heart Block. (10th July 2021) - Abbood, Ali; Al Salihi, Hareer; Parellada, Jorge; Madruga, Mario; Carlan, S. J.
Abstract : Hiatal hernia is a not uncommon anatomic disorder resulting in portions of the bowel occupying space in the thoracic cavity. There are a number of antecedent risk factors including obesity but not hiatal hernias resulting in symptoms. When symptoms do occur, they can include chest pain, nausea, abdominal pain, and gastroesophageal reflux. Cardiac arrhythmias have also been reported as associated conditions resulting from a hiatal hernia. To date, however, a complete heart block secondary to a hiatal hernia has not been reported. An 88-year-old female with a history of GERD (gastroesophageal reflux disease) was found to have a large hiatal hernia at endoscopy after she presented to the emergency department with nausea and abdominal pain. Prior to her scheduled surgical repair, she developed symptomatic third degree heart block which resolved with nasogastric tube deflation of the gastric contents. After surgical repair of the hiatal hernia, she developed episodes of atrial fibrillation with rapid ventricular response and was started on diltiazem. She eventually converted back to normal sinus rhythm and remained dysrhythmia free. In addition to other known arrhythmias associated with hiatal hernia, a complete heart block can also be seen. Acute management requires deflation of the chest occupying hernia. This appears to be the one of the first reported cases of complete heart block caused by hiatal hernia.